Neo-Republicanism: Freedom and Civic Virtue in Philip Pettit and John Pocock - Kunhavalik, Pedro (2014)
This article aims to understand the notion of freedom in the two authors of neo-republicanism, John Pocock and Philip Pettit, and seeks analyze the relationship that the authors establish between political freedom and civic virtue. Pocock works with the prospect of a civic republicanism and advocates the idea that the political participation of citizens and freedom has intrinsic value. Within the republican tradition, Pettit develops the prospect neo-Roman, who understands the political participation so instrumental in the defense of political freedom. The constitutionalism republican, along with contestatory democracy could ensure the ideal of freedom as non-domination.